Build Data Backup with Nextcloud Based Infrastucture as A Service (IAAS) Concept on Budi Darma University - Saidi Ramadan Siregar; Pristiwanto Pristiwanto (STMIK Budi Darma, 2021)
Data or important documents for each lecturer are often neglected in terms of storage and several other cases that cause important document files, for example, rank files, inpasing, certificates, teaching modules, practicum modules that are damaged due to viruses and ransomware when users use the internet using their own laptop. Some other problems include theft, fire, flooding, suddenly damaged laptop, illegible external storage or laptop hard drive, forgetting to backup to Google Drive, forgetting Google Drive password, missing internet package, not being accessed locally and having many problems when the data is somewhere when it's needed. By implementing a centralized data backup in each university with the nextcloud-based Infrastructure As A Service (IAAS) concept, it can provide an alternative to the above problems with the result that 90% of the data will be safe and confidential. Then data access is faster because the server is located in the college area and the data is also held by the respective owner of the lecturer account concerned.